Persistency in Nationalism Found in Rudy Habibie Movie by Hanung Bramantyo - Nurjanah, Mila; Suwarti, T. Sri (Allure Journal, 2023)
This research was written to describe the characterization of Rudy and find the conflicts that exist in the movie so that the writer can find the main points of research that show the persistence in nationalism found in Rudy's struggle in the Rudy Habibie movie. The research focused in persistency in nationalism in Rudy Habibie movie. To analyze this research was made with qualitative and descriptive methods. The writer used the subtitle of the Rudy Habibie movie as the object of research. The results of this research found 3 characterizations that resulted in 8 characters, 3 internal conflicts and 3 external conflicts, and 4 persistence in nationalism. The persistence in nationalism that was found to be very strong where Rudy always tried anything for the good and progress of Indonesia, with persistence in learning, the courage to express opinions, and being willing to part with his first love.